Efficacy and Safety of Vamorolone Over 48 Weeks in Boys With Duchenne Muscular Dystrophy - Utkarsh J. Dang; Jesse M. Damsker; Michela Guglieri; Paula R. Clemens; Seth J. Perlman; Edward C. Smith; Iain Horrocks; Richard S. Finkel; Jean K. Mah; Nicolas Deconinck; Nathalie Goemans; Jana Haberlová; et al. (2024)
Vamorolone is a dissociative agonist of the glucocorticoid receptor that has shown similar efficacy and reduced safety concerns in comparison with prednisone in Duchenne muscular dystrophy (DMD). This study was conducted to determine the efficacy and safety of vamorolone over 48 weeks and to study crossover participants (prednisone to vamorolone; placebo to vamorolone).